Insights Into Interaction Between Clip Device and the Mitral Valve Apparatus in the Human Heart - Takanori Sato, MD, PhD; Issam D. Moussa, MD, MBA; Peter Hanna, MD, PhD; Kalyanam Shivkumar, MD, PhD; Shumpei Mori, MD, PhD (JACC: Case Reports, 2023)
Precise appreciation of the 3-dimensional relationship between the edge-to-edge clips and mitral valve apparatus remains clinically challenging. We demonstrate the images of clips observed in situ 4 years after implantation. Detailed observation from this case helps improve our understanding of 3-dimensional clinical cardiac anatomy related to transcatheter edge-to-edge mitral valve repair. (Level of Difficulty: Intermediate.)